Spatial and temporal shifts in functional and taxonomic diversity of dung beetles in a human-modified tropical forest landscape - Beiroz, Wallace; Sayer, Emma; Slade, Eleanor M.; Audino, Lívia; Braga, Rodrigo Fagundes; Louzada, Julio; Barlow, Jos (Ecological indicators, 2018)
•Conceptually similar indices revealed complex diversity responses to disturbance.•Functional metrics were generally more stable over five-year period than taxonomic.•Using both diversity components better assess its responses to habitat changes. Functional diversity is commonly used to assess the conservation value of ecosystems, but we have not yet established whether functional and taxonomic approaches are interchangeable or complementary to evaluate community dynamics over time and in response to disturbances. We used a five-year dataset of dung beetles from undisturbed forest, primary forest corridors, and Eucalyptus plantations to compare the sensitivity of conceptually equivalent metrics to temporal variation in different anthropogenic disturbances. We compared species richness with functional richness, Pielou’s evenness with functional evenness, and Simpson’s diversity with Rao’s quadratic entropy. We assessed the sensitivity of the metrics to anthropogenic changes. The indices showed complex patterns among habitat types, with with similar responses in some cases and not in other, and little incongruence between the pairs within the same year. The influence of disturbance on longer-term temporal variation over the five-year period revealed lower temporal variation in functional than taxonomic metrics. Both approaches showed greater variation in plantations compared to native forests. We evaluated the variation in taxonomic and functional metrics between consecutive years and among habitats. Most metrics showed similar shifts between years in all habitats, except for species and functional richness. We demonstrate that even conceptually similar indices may not provide similar information on dung beetles responses to disturbance. However, the differences between the indices can yield key insights about the drivers of change, especially over the long-term. It is important to use taxonomic and functional diversity in tandem to better understand community responses to environmental and anthropogenic changes.